67 Suicidality and exposure to school-based violence among a nationally representative sample of Asian American and Pacific Islander youth. (5th May 2020) - Rajan, Sonali; Arora, Prerna
Abstract : Statement of Purpose: Asian Americans and Pacific Islanders (AAPI) are the fastest growing racial/ethnic minority group in the U.S. However, less focus has been paid to the rates of suicidal behaviors among AAPI youth, despite estimates placing suicide as the second leading cause of death among AAPI youth (15–24 years). At the same time, exposure to school-based violence has a long-term negative impact on youth outcomes. And recent research has noted that AAPI youth are more likely to be victimized in schools than their non-AAPI peers. The current study expands on the limited existing research and examines the relationship between suicidal behavior and exposure to school-based violence among a national sample of AAPI high school students. Methods: We conducted a secondary analysis of the CDC's most recent Youth Risk Behavior Surveillance System data (n=14, 765). Results: Results demonstrated that the prevalence of AAPI youth engaging in suicidal behaviors does not differ significantly from other demographic subgroups. Further, a significant correlation between exposure to school-based violence (including having been threatened with a weapon and a perceived lack of safety at school) and four suicidal behaviors was observed among this sample of AAPI youth: considered suicide attempt: r=0.237, p< 0.001; made a suicide plan: r=0.237, p< 0.001; attempted suicide: r=0.164, p<0.001, had a suicide attempt that resulted in injury: r=0.147, p<0.001. Conclusions: Our findings confirm that AAPI youth are engaging in suicidality behaviors and experiencing school-based violence at rates comparable to non-AAPI youth. We also demonstrate that a significant relationship between exposure to school violence and suicidality persists for this subgroup. Significance: Implications for integrating existing mental health practices with school-based violence prevention efforts and that are tailored specifically to the needs of AAPI youth are discussed.